Phytoplankton Community Structure in Seagrass Beds in Tiwoho Village, North Minahasa Regency - Rimper, Abraham M.; Warouw, Veibe; Rimper, Joice R.T.S.L; Lintang, Rosita A.J.; Ompi, Medy; Pangkey, Henneke D. (Sam Ratulangi University, 2023)
This research was carried out from May to July 2022. A sampling at the study site included seawater for the needs of plankton identification as well as the measurement of water nitrate & phosphate levels and measurement of physical and chemical parameters such as temperature, pH, salinity and dissolved oxygen which were carried out on an ongoing basis In situ (in the field). The technique for determining plankton sampling was carried out purposively, namely with certain considerations to obtain samples that represent the research location area. Plankton sampling was carried out horizontally using a plankton net. Sample bottles containing seawater were identified at the Marine Biology Laboratory, Faculty of Fisheries and Marine Sciences. The composition of the phytoplankton found in the Tiwoho seagrass bed ecosystem consists of three classes, namely the Bacillariophyceae, Dynophyceae, and Cyanophyceae classes, with 28 genera. The results of chopped phytoplankton are expressed in Cells/l. The qualitative determination of plankton is made up to the genus level. The composition of the phytoplankton found in the Tiwoho seagrass bed ecosystem consists of three classes, namely the Bacillariophyceae, Dynophyceae, and Cyanophyceae classes, with 28 genera. The results of calculating the abundance of phytoplankton in the Tiwoho seagrass ecosystem are in the range of 29 - 66 cells/l. The highest abundance was found at station two, namely 66 cells/l with 21 genera, then station three (65 cells/l) with 24 genera, and station one (29 cells/l) with a total of 23 genera. The diversity index of seagrass beds in Tiwoho waters is in the range of 1.9330 - 2.4083, which means that community stability is categorized as moderate. The uniformity index is in the range of 0.4614 - 0.7154, this means that the uniformity between species is relatively the same, or the difference is not striking. While the domination index is in the range of 0.1494 - 0.2404, it means that the condition of the community structure is stable, and there is no ecological pressure (stress) on biota. Keywords: Phytoplankton, Biological Index, Abundance, Environmental parameters Abstrak Penelitian ini dilaksanakan pada bulan Mei sampai bulan Juli 2022. Pengambilan sampel di lokasi penelitian meliputi air laut untuk kebutuhan identifikasi fitoplankton dan pengukuran kadar nitrat, fosfat perairan serta pengukuran parameter fisika kimia seperti suhu, pH, salinitas dan oksigen terlarut yang dilakukan secara In situ (di lapangan). Teknik penentuan pengambilan sampel plankton dilakukan secara purposif yaitu dengan pertimbangan tertentu untuk mendapatkan sampel yang mewakili area lokasi penelitian. Pengambilan sampel plankton dilakukan secara horisontal dengan menggunakan plankton net. Sampel plankton diberi pengawet formalin 4% dan diidentifikasi di laboratorium Biologi Kelautan Fakultas Perikanan dan Ilmu Kelautan. Komposisi fitoplankton yang dijumpai di ekosistem padang lamun Perairan Tiwoho terdiri dari tiga kelas yaitu kelas Bacillariophyceae, Dynophyceae, dan Cyanophyceae, dengan 28 genera. Hasil perhitungan kelimpahan fitoplankton di ekosistem padang lamun Perairan Tiwoho berada di kisaran 29 - 66 sel/l. Kelimpahan tertinggi ditemukan di stasiun dua (depan kampung) yaitu 66 sel/l dengan 21 genera, kemudian stasiun tiga (depan dermaga) yaitu 65 sel/l dengan 24 genera, dan stasiun satu (ujung kampung) sebanyak 29 sel/l dengan jumlah 23 genera. Indeks keanekaragaman ekosistem padang lamun Perairan Tiwoho berada pada kisaran 1,9330 - 2,4083, yang berarti stabilitas komunitas dikategorikan sedang. Indeks keseragaman yaitu pada kisaran 0,4614 - 0,7154, ini berarti keseragaman antar spesies relatif sama, atau perbedaannya tidak menyolok. Sedangkan indeks dominasi yaitu pada kisaran 0,1494 - 0,2404, berarti kondisi struktur komunitas dalam keadaan stabil, dan tidak terjadi tekanan ekologi (stress) terhadap biota. Kata kunci: Fitoplankton, Indeks Biologi, Kelimpahan, Parameter lingkungan